Study by Europe’s Leading Language Technology Experts Warns Most European Languages Unlikely to Survive in the Digital Age - Rehm, Georg; Uszkoreit, Hans (Infotheca - Journal for Digital Humanities; Vol 13 No 2 (2012): Infotheca - Journal of Informatics and Librarianship, 2024)
Most European languages face digital extinction, a new study by Europe’s leading Language Technology experts finds. Assessing the level of support through language technology for 30 of the approximately 80 European languages, the experts conclude that digital support for 21 of the 30 languages investigated is “non-existent” or “weak” at best. The study was carried out by META-NET, a European network of excellence that consists of 60 research centres in 34 countries.